Corrosion inhibition efficiency of moringa leaf extract (Moringa oleifera) against A36 steel - Rita Desiasni; Mardiana Mardiana; Syamsul Hidayat (Jurnal Pijar Mipa, 2021)
The use of inhibitors is one of the most effective ways to control corrosion. The study aims to determine and examine more deeply the effect of variations in the concentration of organic inhibitors from Moringa leaf extract on the corrosion rate of A36 steel material in seawater media. Moringa leaf extract's effectiveness in inhibiting the corrosion rate of A36 steel material in seawater media is also determined. This research was conducted by immersing specimens with inhibitor concentrations of 0 ppm, 100 ppm, 200 ppm, 300 ppm, 400 ppm, and 500 ppm for seven days of immersion. The corrosion rate is calculated using the weight loss method. The results showed that the corrosion rate decreased with the inhibitor concentration in the corrosion media. The inhibitor concentration of 500 ppm Moringa leaf extract was able to inhibit the corrosion rate optimally. It is indicated by the smallest corrosion rate value of 1.07 mpy. On the other hand, the inhibitor efficiency increases with the inhibitor concentration in the corrosion media. The highest inhibitor efficiency was 78.71% at the addition of 500 ppm inhibitor to the solution.